Ramifications of Roadways Conditions and Traffic Features on Roads Safety : A Safety Perspective for Jalandhar, Punjab - Pandey, Kushagra; Bhardwaj, Nitin (AMC Indian Journal of Civil Engineering, 2020)
India is in a developing phase and safety on roads is at a premature stage. Accidents are increasing day by day leading to a great loss of life. Some people are disabled, others suffer damage to property and health, and degradation of environment resulting in a situation in India that is at a tocsin stage. Official records show that approximately 1,42,000 persons were killed and approximately 4,80,000 injured in traffic accidents in India in 2014 (NCRB 2015). However, this is underestimated since many accidents are off the records and all accidents are not reported. The high accident rate is due to inadequacy of highways and GT roads which cannot meet traffic demands or some other reasons like vehicular defect, poor road geometry or road user behaviour. These accidents deal a heavy blow to the economy of a country. Hence, road safety is a necessity for reduction in accidents.